KERAGAMAN SPESIES HERBA-LIANA DAN KEMIRIPAN KOMUNITASNYA DI AREA REKLAMASI PT ADARO INDONESIA, PROVINSI KALIMANTAN SELATAN, INDONESIA - Aqdestiasari Nahdia Ulfah; Mochamad Arief Soendjoto; Setia Budi Peran; Fazlul Wahyudi (Jurnal Sylva Scienteae, 2020)
The four locations in the PT Adaro Indonesia reclamation area have never been investigated before, so the herb-liana species were also unknown. The purpose of this research was to identify herb-liana species in the reclamation area of the former coal mine and analyze the diversity of species and similarity of the community. Ten plots were made at each location. On a virtual line that extends at a location, one point was randomly determined and used as the initial angle to make a plot (5 m x 5 m). Plot was placed on the left part of the virtual line and one of the plot sides was aligned with the virtual line. At a distance of 20 m from the starting point, the second point was placed, which then become the starting angle for the second plot (5 m x 5 m). Plot was placed on the right part of the virtual line and one of second plot sides was aligned with the virtual line. And so on until 10 plots were formed alternately on the left and right of the virtual line. From these plots, all species of herb-liana were identified and the individual number of each species was accounted. The data was processed so that the Shannon-Wienner diversity index (H ') and the Jacard similarity index (SJ) were obtained. Thirty-four species (15 families) of herb-liana were identified and 1 species was not identified. Species spread differently between certain locations and other locations. Centrosema pubescens dominates 3 locations whose revegetation age is under 5 years, while Asystasia gangetica is only 1 location whose revegetation age is around 5 years. Although the community similarity index values calculated according to the number of species differ from those calculated according to the INP, the results remain the same that the lowest similarity index occurs between Location 1 and Location 3, while the highest is between Location 1 and Location 2.